1995
DOI: 10.1074/jbc.270.41.24406
|View full text |Cite
|
Sign up to set email alerts
|

Molecular Cloning, Structure, and Expression of Mouse Estrogen-responsive Finger Protein Efp

Abstract: We have previously identified a human estrogen-responsive gene, efp (estrogen-responsive finger protein), which encodes a putative transcription regulator (Inoue, S., Orimo, A., Hosoi, T., Kondo, S., Toyoshima, H., Kondo, T., Ikegami, A., Ouchi, Y., Orimo, H., and Muramatsu, M. (1993) Proc. Natl. Acad. Sci. U. S. A. 90, 11117-11121). Here, we report isolation of mouse Efp cDNA and its structure containing three cysteine-rich domains (RING finger and B1 and B2 boxes), a coiledcoil domain, and a C-terminal domai… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
53
0

Year Published

1997
1997
2020
2020

Publication Types

Select...
8

Relationship

1
7

Authors

Journals

citations
Cited by 69 publications
(54 citation statements)
references
References 55 publications
1
53
0
Order By: Relevance
“…The positive immunohistochemical staining for ER was observed in the nuclei of glandular and luminal epithelium and myometrium in rat uterus. This result was consistent with previous reports (Zaino et al 1989, Hild-Petito et al 1988, Hild-Petito et al 1992, Koji & Brenner 1993, Orimo et al 1995, Saunders et al 1997. The staining of ER was detected in the nuclei of glandular epithelium in rat uterus, whereas no staining was detected in luminal epithelium and myometrium.…”
Section: Discussionsupporting
confidence: 83%
See 2 more Smart Citations
“…The positive immunohistochemical staining for ER was observed in the nuclei of glandular and luminal epithelium and myometrium in rat uterus. This result was consistent with previous reports (Zaino et al 1989, Hild-Petito et al 1988, Hild-Petito et al 1992, Koji & Brenner 1993, Orimo et al 1995, Saunders et al 1997. The staining of ER was detected in the nuclei of glandular epithelium in rat uterus, whereas no staining was detected in luminal epithelium and myometrium.…”
Section: Discussionsupporting
confidence: 83%
“…Data from several laboratories, using in situ hybridization or immunohistochemistry, have shown that the ER localizes in granulosa cells and theca cells in certain species (Kudolo et al 1984, Iwai et al 1991, Billiar et al 1992, Orimo et al 1995, Byers et al 1997. Saunders et al (1997) were unable to demonstrate the presence of ER in rat granulosa cells by immunohistochemistry.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Furthermore, the expression of the estrogenresponsive finger protein (efp) is regulated during osteoblast differentiation (71). The ability of these proteins to induce differentiation could be related to their DNA binding properties, suggesting a role in transcriptional regulation, as described previously for efp (72). However, the sequences of the promoters targeted by these factors remain to be determined.…”
Section: Fig 5 Expression Of Enterophilin-1 Along the Small Intestimentioning
confidence: 95%
“…4 In mice, estrogen-induced expression of Efp is observed in tissues such as uterine tissue. 5 Efp-deficient mice exhibit underdeveloped uteri and reduced estrogen responsiveness. 6 In human MCF-7 breast cancer cells, the expression of Efp mRNA is induced in response to estrogen.…”
Section: Introductionmentioning
confidence: 99%